COMPREHENSIVE ANALYSIS OF TELEHEALTH IMPLEMENTATION IN HEALTHCARE DELIVERY AND EXAMINING BENEFITS, CHALLENGES, AND BEST PRACTICES - 1Ibrahim Salem Mutlaq Balhareth, 2Mahdi Zadin Zamy Alzbadeen, 3Mansour Nasser Al Hermis, 4Faras Hamed Hadi Almanjam, 5Saeed Saleh Muhammad Zabadin, 6Hassan Nasser Shelwan Alzabadeen, 7Dhafer Mansour Monassar Al Salem, 8Salem Ali Mohammed Alrabai, (Chelonian Research Foundation, 2022)
Telemedicine, the inaccessible arrangement of restorative administrations through communications innovation, has been expanding consideration for a long time, particularly in reaction to the widespread COVID-19. This article gives a comprehensive audit of the use of telemedicine in healthcare, investigating its benefits, challenges, and best practices. A comprehensive writing survey investigated different viewpoints of telemedicine utilization, counting patients results, nurses fulfillment, innovation utilization, and regulatory lament results. Strategies for assessing telemedicine viability and methodologies for optimizing telemedicine utilization are examined. The comedies and discoveries, displayed with pictures, tables, and charts, outline the different impacts of telemedicine on healthcare and patients care. The dialog investigates the effects of telemedicine appropriation on healthcare conveyance, quality, and value. Finally, proposals were made to improve in integrating telemedicine into healthcare frameworks, illuminate issues, and increase the advantages for patients and benefit providers. Keywords: Telehealth, healthcare delivery, remote healthcare, benefits, challenges, best practices.